Childhood encephalitis in the United Kingdom - epidemiology, trends in hospital admissions and the role of intravenous immunoglobulin - Iro, M (2018)
The burden from childhood encephalitis is significant, 30-60% of affected children develop long term disability despite treatment. Crucial to improving outcomes are a better understanding of the disease epidemiology, and the identification of alternative treatment strategies. To contribute to ongoing work currently addressing these issues globally, I conducted a 30-year review of childhood encephalitis hospital admissions in England, and also a 10- year review of paediatric intensive care unit (PICU) admissions in England and Wales (E&W;). Through these projects, I defined the incidence of all-cause childhood encephalitis in England, and severe encephalitis in E&W.; I described hospital admission trends for childhood encephalitis in England, and evaluated how these had varied with introduction of the combined measles, mumps, rubella vaccine. Furthermore, I estimated the potential cost burden from encephalitis PICU admissions, and identified factors associated with mortality and length of stay on PICU in children with severe encephalitis. This thesis provides high quality data from a Cochrane systematic review on the role of intravenous immunoglobulin (IVIG) treatment in childhood encephalitis, and describes the initiation of the first ever randomised controlled trial (RCT) of IVIG all-cause childhood encephalitis (IgNITE). The incidence for all-cause childhood encephalitis in England was between 2.91/100,000/year (95%CI 2.80-3.14) and 4.02/100,000/year (3.80-4.28), and the incidence of severe childhood encephalitis in E&W; was 0.79/100,000/year (0.74-0.84). An increasing trend in encephalitis admissions was observed between 1999-2011, compared to the previous years. This increase was most marked in infants, and mostly seen in the ‘encephalitis of unknown aetiology’ group. Measles and mumps encephalitis admissions reduced by 30-fold after the two dose MMR vaccination schedule was introduced, compared with the pre MMR period. The PICU encephalitis bed cost was ~£414,000/year. The Cochrane review revealed paucity of RCTs of IVIG in encephalitis. Although the findings indicated some benefit from IVIG, the quality of the evidence was very low. Accordingly, I initiated the first ever RCT of IVIG treatment in all-cause childhood encephalitis, which had recruited 18 participants from 21 sites. Data from an interim analysis of this cohort showed that 60% were admitted to PICU, and 89% required invasive ventilation. Also, 80% of affected children had persisting symptoms at hospital discharge, 67% made poor recovery at 4-8 weeks after hospital discharge while 42% and 30% made poor recovery at 6 and 12 months follow up, respectively. The increasing trend in childhood encephalitis admissions in the context of the ongoing threat from emerging and reemerging pathogens, indicates the need for continued disease surveillance. The findings of the systematic review rationalise the need for the IgNiTE study. The results of the interim analysis of data from the IgNiTE trial indicate the need to identify strategies to improve outcomes in children with encephalitis. It is anticipated that the IgNiTE trial would yield results that could alter the way that children with encephalitis are managed.